Digitalisasi Sistem Penjaminan Mutu Internal (SPMI) untuk Institusi Pendidikan Berbasis Website - Cevin, Jery; Gultom, David; Hermawan, Latius (Universitas Multi Data Palembang, 2025)
In the current era of digital development, an internal quality assurance system (SPMI) is essential to improve the quality of education. However, the manual methods still used are often inefficient and prone to errors, and this research aims to develop a digital-based SPMI system to improve data management as well as quality evaluation. The rapid application development (RAD) method used in this project enables rapid and iterative system development. Digitalization of quality standard documents, evaluation data management, and monitoring dashboard are the main features of the developed system. Test results show that the system can improve the efficiency of the quality assurance process by improving data integration and reducing manual work. With this system, it is expected to be able to conduct better quality monitoring and evaluation and become a model for other institutions for SPMI digitization.